Second-Trimester Dilation and Evacuation: A Simulation-Based Team Training Curriculum - Leah N. Schwartz; Andrea Pelletier; Alisa B. Goldberg; Kari Braaten; Brian Donnenfeld; Jennifer Muller; Persephone Giannarikas; Nancy Falconer; Deborah Campbell; Deborah Bartz (Association of American Medical Colleges, 2023)
Introduction Despite the need for providers skilled in second-trimester dilation and evacuation (D&E) procedures, there are few second-trimester abortion training opportunities for OB/GYN residents and other health care trainees. Barriers to such training include restrictive state laws and institutional policies, lack of trained faculty, and limited procedural volume. Simulation-based D&E training is, therefore, a critical tool for OB/GYN residents and other medical professionals to achieve clinical competency. Methods This simulation for OB/GYN residents centers on a 29-year-old woman at 18 weeks gestation with intrauterine fetal demise, requiring learners to perform a second-trimester D&E and manage an unexpected postprocedural hemorrhage. We designed the simulation to be used with a high-fidelity mannequin. Personnel roles required for the simulation included an anesthesiologist, medical assistant, OR nurse, and two OB/GYN faculty. Learner performance was assessed using a pre- and postsimulation learner evaluation, a critical action checklist, and a focus group with simulation facilitators. Results Forty-nine residents participated over an 8-year period. Learners demonstrated improved competency performing a second-trimester D&E and increased confidence managing postprocedural hemorrhage after participating in this simulation. In addition, focus group participants reported that a majority of learners demonstrated confidence and effective communication with team members while performing in a decision-making role. Discussion In addition to improving learners' clinical competency and surgical confidence for second-trimester D&E procedures, this simulation serves as a valuable instrument for the standardized assessment of learners' performance, as well as an opportunity for all participants to practice teamwork and communication in a high-acuity setting.